2012
DOI: 10.1007/s00405-012-2112-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of video-endoscopy on the results of retrosigmoid-transmeatal microsurgery of vestibular schwannoma: prospective study

Abstract: Endoscopy-assisted microsurgery represents modern trend of treatment of the cerebellopontine angle (CPA) pathologies including vestibular schwannoma (VS). Endoscopes are used in adjunct to microscope to achieve better functional results with less morbidity. Angled optics, magnification and illumination enable superior view in the operative field. Consecutive 89 patients with untreated unilateral sporadic vestibular schwannoma undergoing tumor resection via a retrosigmoid approach during 2008-2010 were prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 12 publications
0
29
0
2
Order By: Relevance
“…The same is true for the retrosigmoid-transmeatal approach in which the most common pathways of leak formation are perimeatal air cells of petrous bone; therefore, their sealing is crucial for CSF leak prevention. The addition of endoscopic and endoscopy-assisted vestibular schwannoma surgery seems to be beneficial for improved identification of potential pathways of CSF leakage [34]. The material used for petrous bone air cells sealing can also be considered a significant factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same is true for the retrosigmoid-transmeatal approach in which the most common pathways of leak formation are perimeatal air cells of petrous bone; therefore, their sealing is crucial for CSF leak prevention. The addition of endoscopic and endoscopy-assisted vestibular schwannoma surgery seems to be beneficial for improved identification of potential pathways of CSF leakage [34]. The material used for petrous bone air cells sealing can also be considered a significant factor.…”
Section: Discussionmentioning
confidence: 99%
“…Overall incidences of persisting postoperative vertigo and disequilibrium in VS microsurgery have ranged from 1% to as high as 30% [16, 69, 81]. In our previous study [34], the patient's age was identified as the only important factor associated with disordered vestibular compensation following retrosigmoid VS microsurgery. Thus, new methods including prehabituation and biofeedback seem to be a logical step of outcome improvement [72, 77].…”
Section: Discussionmentioning
confidence: 99%
“…Better exposure encourages for less drilling of the posterior wall of the IAM which consequently will reduce the risk of injury to endolymphatic duct, common crus, vestibule or ampulla of the posterior semicircular canal (Domb and Chole, ). Early endoscopic inspection supports identification of tumor extension, neurovascular structures and relationships, the proximity of the jugular bulb and the fundus of the IAM (Gerganov et al, ; Göksu et al, ; Chovanec et al, ). Accidentally opened mastoid cells can easily be identified and sealed to prevent postoperative CSF fistula (Göksu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…1 The most common cause of CSF leakage regardless of approach is unrecognized open air cells during drilling. 1,3,7 Other morbidities that may arise from the retrosigmoid approach include injury to the cerebellum, cranial nerves, and vessels; headache; and hearing loss despite saving the cochlear nerve anatomy. 4 The hearing loss may be the result of an injury to the posterior semicircular canal during the surgeon's attempt to expose the internal acoustic canal (IAC) posteriorly.…”
Section: Introductionmentioning
confidence: 99%